Efek diet tinggi lemak terhadap berat testis dan kadar glukosa darah puasa tikus Wistar jantan - Rista Dwi Hermilasari; Septy Handayani; Ellanda Rima Ervyanna (Poltekkes Kemenkes Aceh, 2026)
Background: Globally, modern lifestyle trends are characterized by increased consumption of high-fat food, which contribute to metabolic disorders. High-fat diets can also cause disorders in the male reproductive system. However, evidence regarding the association between changes in testicular weight and glycemic dysregulation as indicators of metabolic-reproductive disorders in animal studies remains limited.Objectives: This study aimed to evaluate the effect of high-fat diet on testicular weight and fasting blood glucose levels inmale Wistar rats.Methods: This study was conducted in June toJuly 2024 at the Basic Dentistry Laboratory, University of Jember using a randomized posttest-only control group design. A total of 14 male Wistar rats were divided into two groups: P1 (normal diet) and group P2 consisting of 2 ml of egg yolk given for 28 days. The rats were provided with drinking water ad libitum. Fasting blood glucose levels were measured using an Easy Touch GCU glucometer. After the rats were euthanized and dissected, testicular weight was measured using a digital scale with an accuracy of 0,1 g. Data were analyzed using an independent t-test with a significance value of p < 0.05.Results: Administration of a high-fat diet to male Wistar rats showed lower testicular weight compared with the normal diet group, but the difference was not statistically significant (p = 0.315).In contrast , administration of high-fat diet to Wistar rats showed a significant difference in fasting blood glucose levels compared the normal diet group (p < 0.001).Conclusion: A high-fat diet significantly increases fasting blood glucose levels, indicating impaired glucose homeostasis and potentially contributing to changes in testicular weight, which may disrupt reproductive function.